How “unequal treaties” influenced commission competence: a new perspective on the United Nations Convention on the Law of the Sea (Part XV) in the Timor Sea Conciliation - Jing, Ming (Frontiers in Marine Science, 2024)
The United Nations Convention on the Law of the Sea (UNCLOS) is a widely ratified multilateral treaty that defines and codifies the standards and principles of international law for the governance and management of the oceans. One of its key features is the facilitation of the peaceful settlement of disputes on maritime affairs. Article 281 constitutes an equality test by which the courts or tribunals can distinguish voluntary procedures from compulsory proceedings. Existing cases under Part XV did not provide a clear routine what circumstances might make a treaty under Article 281 "unequal". Article 311 deals with the tension between prioritizing the regional arrangements and maintaining UNCLOS as a closed, self-contained system. This research aims to provide insights into the proper application of these two articles in future UNCLOS disputes, as the Timor Sea Conciliation (Timor-Leste v. Australia) is the first instance of the conciliation mechanism under UNCLOS. Through the methods of doctrinal research and comparing the different argumentations in previous cases, the research found that the recent Timor Sea Conciliation was decided on the basis of a controversial understanding of UNCLOS Articles 281 and 311; that a treaty featuring specific and feasible arrangements for dispute settlement would be easier in passing Article 281's test; and that Article 311 favors UNCLOS's integrity and considers the permitted derogations as exceptions. It is suggested that the courts or tribunals under UNCLOS Part XV interpret Articles 281 and 311 in a systematic manner, which is believed to benefit the development of voluntary dispute settlement mechanism under UNCLOS in the long run.